the THE ROLE OF SHARED LEADERSHIP TOWARDS INDIVIDUAL INNOVATION IN WORK MEDIATED BY AMBIDEXTERITY AND QUALITY MANAGEMENT IN THE PND ICE MAKING SYSTEM: - - Wibowo, Bobby; Antonio, Tony (International Journal of Review Management Business and Entrepreneurship (RMBE), 2024)
This study aims to examine the role of Shared Leadership on Individual Innovation in working in mediation by Ambidexterity and Quality Management at the PND Ice Making Systems company. The variables studied were Shared Leadership (X1), Ambidexteruty (Z1), Quality Management (Z2) and Individual Innovation (Y). The analytical tool used is analysis using SEM-PLS. The population in this study used a saturated sampling technique, namely all PND Ice Making Systems employees totaling 50 respondents. The results showed that Shared Leadership has a significant and positive effect on Ambidexterity, Ambidexterity has a significant and positive effect on Individual Innovation in PND, Quality Management has a significant and positive effect on Ambidexterity, Shared Leadership has a significant and positive effect on Quality Management, Shared Leadership has a significant and positive effect on Individual Innovation mediated by Ambidexterity significantly and positively, Shared Leadership has a significant and positive effect on Individual Innovation mediated by Ambidexterity and Quality Management